Analysis of Organizational Culture and Job Satisfaction on Employee Performance - Rauf, Rusdiaman; Pajala, Semuel; Asirie, Ronny Ahmad (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2024)
This study aims to determine the influence of organizational culture and job satisfaction on the performance of employees of the Mamasa Regency Food Security Office, West Sulawesi. The type of research approach used in this study is quantitative research, namely research where data collection is in the form of numbers and analysis using statistics. The population in this study is State Civil Apparatus Employees at the Mamasa Regency Food Security Office, the analysis methods used are multiple regression analysis, t-test analysis, f-test analysis, correlation analysis and determination analysis. The results of the study showed that (i) organizational culture partially had a positive and significant effect on employee performance, (ii) job satisfaction partially had a positive and significant effect on employee performance, and (iii) organizational culture and job satisfaction simultaneously affected employee performance in employees of the Mamasa Regency Food Security Office.